(untitled) (JOURNAL OF ANALYTICAL SYNERGY AND SCIENTIFIC HORIZON, 2025)
This article examines the influence of self-confidence on children’s academic achievement. It discusses how self-belief affects students’ motivation, participation, ability to overcome challenges, and emotional well-being. The article argues that strong self-confidence helps children perform better at school, while low confidence can negatively impact their learning. Suggestions for supporting children’s self-confidence are also provided.